Fine-scale tribological performance of zeolitic imidazolate framework (ZIF-8) based polymer nanocomposite membranes - Nay Win Khun; E. M. Mahdi; Siqi Ying; Tan Sui; Alexander M. Korsunsky; Jin-Chong Tan (APL Materials, 2014)
We combined zeolitic imidazolate framework nanoparticles (ZIF-8: ˜150 nm diameter) with Matrimid® 5218 polymer to form permeable mixed matrix membranes, featuring different weight fractions of nanoparticles (up to 30 wt. % loading). We used ball-on-disc micro-tribological method to measure the frictional coefficient of the nanocomposite membranes, as a function of nanoparticle loading and annealing heat treatment. The tribological results reveal that the friction and wear of the unannealed samples rise steadily with greater nanoparticle loading because ZIF-8 is relatively harder than the matrix, thus promoting abrasive wear mechanism. After annealing, however, we discover that the nanocomposites display an appreciably lower friction and wear damage compared with the unannealed counterparts. Evidence shows that the major improvement in tribological performance is associated with the greater amounts of wear debris derived from the annealed nanocomposite membranes. We propose that detached Matrimid-encapsulated ZIF-8 nanoparticles could function as “spacers,” which are capable of not only reducing direct contact between two rubbing surfaces but also enhancing free-rolling under the action of lateral forces.